(3GdeSGFd (B( (3aj Yde CMcGe GdfLhe(B)s - (3CHh jhSa jYbhH Hf Ydj GdbQTj GdbUQGfj, GdbUQGfj,J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hhLOJ ajeG ZHQ Hg Yf GdChdjf eeG ChOYJ cJHgG ef SQgG Gdecfhf eQGJH GdYde KdGKI CYdGgG GdeYQaI hgh Yde GdJhMjO s
(3BNQgG (B:s
(3Ch jfXQ Edi GdSYhO ajchf cPdc GdTF GdPi jSCd Yfg aQMkG hUdGMkG HEPf Gddg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQgG ahGFO adcjI HebOGQ YTQ hQbGJs
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3fbdJ gPg GdfSNI Yf fSNjJf HcJH NGfI GdNOjhjI GdeUQjI HeUQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdadcs